Method for separating and purifying cycloolefin resin material from recycled plastic

By dissolving and recycling plastics with mixed solvents at specific temperatures and times, and combining adsorbents and precipitants to treat, the problem of separation and purification of cycloolefin resin materials is solved, and high-purity recycling of cycloolefin resin materials is achieved, which is suitable for high-end fields.

CN119798775AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510000370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and environmentally friendly separation and purification of cycloolefin resin materials, especially COC and COP, resulting in limited applications in high-end fields.

Method used

The plastic is recycled by dissolving and recycling of plastics with mixed solvents (decahydronaphthalene and dimethyl sulfoxide) under specific temperature and time conditions, and combining adsorbent and precipitant treatment, the relationship between temperature and residence time is optimized, so as to achieve efficient separation and purification of cycloolefin resins.

Benefits of technology

It improves the purity and recovery rate of cycloolefin resin materials, reduces energy consumption, is suitable for high-end fields, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798775A_ABST
    Figure CN119798775A_ABST
Patent Text Reader

Abstract

The invention provides a method for separating and purifying a cycloolefin resin material, which is characterized in that recycled plastic is maintained in a solvent at a certain temperature and for a certain time, and the temperature and the time meet the following limited relation, so that the cycloolefin resin material in the recycled plastic is fully dissolved in the solvent; # imgabs0 # n is greater than or equal to 0; wherein T0 and Tn are respectively a certain specific temperature and a next increased temperature; t0 and tn are respectively residence time corresponding to specific temperatures T0 and Tn, and when T0 is 60 DEG C, t0 is 40 min. According to the scheme, COC and COP plastics in the plastics can be separated, purified and recycled, the used solvent does not contain carcinogenic solvents such as methylbenzene and benzene, the good environment-friendly property is achieved, and the obtained regenerated COC and COP products have excellent transparency and high application value under the condition that no additional auxiliaries are added, and can be used in the high-end fields such as food packaging and medical packaging. In addition, separation and purification of COC or COP materials can be met at the same time, and the additional value of recycled cycloolefin resin materials is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer material technology and plastic recycling, and in particular to a method for separating and purifying cycloolefin resin materials and its application. Background Art

[0002] The treatment of waste plastics and the corresponding environmental issues have received widespread attention from the public and professionals. Therefore, the recycling of waste plastics has become an important direction, especially polyolefin materials are widely used in the field of food packaging. The volume used and discarded each year is very large, causing serious environmental pollution. Therefore, the recycling of film packaging materials is the most important way to solve plastic pollution. It can also save energy, reduce the consumption of petrochemical energy, and effectively solve the environmental pollution and ecological crisis problems faced. Cyclic olefin resin materials include cycloolefin copolymers (COC) and cycloolefin polymers (COP). As a class of high-end polyolefin resins in the polyolefin material family, they are widely used in many packaging fields for their excellent properties such as water vapor barrier, fragrance retention, high permeability, and dead fold. Therefore, the recycling and reuse of cycloolefin resin materials has become crucial.

[0003] As we all know, there are different ways to recycle plastics, including mechanical recycling, advanced physical or solvent recovery, and chemical processing (such as thermochemical recovery such as pyrolysis or gasification and solvent decomposition). Mechanical recycling refers to the recycled polyolefin materials obtained by simple physical and mechanical treatment of waste polyolefin plastics such as direct blending, melt blending, extrusion granulation, etc. However, polyolefin plastics usually degrade during this process, resulting in obvious yellowing of the material, a sharp decrease in transparency, and serious attenuation of mechanical properties. They cannot be used in high-end fields and can only be recycled in low-value products. High-temperature chemical cracking refers to the pyrolysis reaction of polyolefin plastics under the action of heating and catalysts, which causes the polymer chains to break indiscriminately to form low-molecular substances, but less monomers are formed, and they cannot be used as monomers again in polyolefin synthesis later. In addition, the chemical depolymerization process is complicated, and the high temperature conditions have extremely high requirements for industrialization, high carbon emissions, huge energy consumption, and high costs.

[0004] Solvent recovery avoids the significant attenuation of material properties caused by mechanical recovery, as well as the problems of complex high-temperature cracking process and high energy consumption. Patent CN107810226B reports that short-chain aliphatic hydrocarbon solvents can dissolve polyolefin plastics under high temperature and high pressure, but the process is harsh, requires high temperature and high pressure conditions, and has high energy consumption; Patent CN114133618B reports that low-density polyethylene resin can be dissolved using a compound solvent (toluene / limonene), while COC is insoluble, and high-purity COC recycled material can be obtained after filtration, but toluene is highly toxic and pollutes the environment, and long-term contact will affect the health of personnel, making the recycled COC material unable to be used in high-end fields such as food packaging and medical packaging, and this method is only suitable for recycling COC materials, and cannot take into account the recycling of COP materials.

[0005] In summary, the art urgently needs to develop a simple, efficient, green, environmentally friendly, and low-energy method for purifying cycloolefin resin materials, which is suitable for separating and purifying COC materials and for purifying COP materials, so as to meet the demand for recycled cycloolefin resin material products in the high-end field. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for separating and purifying cycloolefin resin materials, which is particularly suitable for separating and purifying plastic recycling materials mainly composed of COC or COP. A method for separating and purifying solvents used for cycloolefin resins is provided, and the relationship between temperature and time is cleverly established. The residence time is controlled according to the temperature, which can not only give play to the advantages of high recovery rate, but also make the purity of recycled plastics high. Compared with other cycloolefin resin recycled materials, it is improved, has high application value, and has the advantages of simplicity, high efficiency, green environmental protection, low energy consumption and low cost.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for separating and purifying cycloolefin resin materials from recycled plastics, the method comprising maintaining the recycled plastics in a solvent at a certain temperature and time, wherein the temperature and time satisfy the following defined relationship, so that the cycloolefin resin materials in the recycled plastics are fully dissolved in the solvent; n ≥ 0;

[0009] Where T0 and T n are a certain temperature and the next elevated temperature; t0 and t n They correspond to specific temperatures T0 and T n The next dwell time.

[0010] In the present invention, when T0 is 60°C, t0 is 40min; when T1=70°C, When T2 = 80°C, When T3 = 90 °C, 0.833 × [40 / (e 2 )]min≤t3≤40 / (e 2 )min, when T4=100℃,

[0011] In the present invention, the cycloolefin resin material is cycloolefin copolymer (COC) or cycloolefin polymer (COP).

[0012] In the present invention, when T0=60°C, t0=40min; the heating temperature T is controlled at 60-100°C, for example, 60, 70, 80, 90, 100°C; the residence time t is controlled at 2.3-40min, for example, 2.3, 10, 20, 30, 40min.

[0013] In the present invention, the solvent is a mixed solvent selected from decalin and dimethyl sulfoxide or tetralin and dimethyl sulfoxide.

[0014] In the present invention, the volume fraction of decalin is 68-80% of the total volume of the mixed solvent, and the volume fraction of tetralin is 53-63% of the total volume of the mixed solvent.

[0015] In a specific embodiment, the method for separating and purifying cycloolefin resin material of the present invention comprises the following specific steps:

[0016] ② Wash, dry and deep-cryogenically crush the recycled plastics to obtain waste powder;

[0017] ② Mix the waste powder with the solvent, heat it to a certain temperature under stirring conditions and keep it for a specific time;

[0018] ③ adding an adsorbent to the mixed material of step ② for adsorption, and then collecting to obtain a purified cycloolefin resin solution;

[0019] ④ Add a precipitant to the purified cycloolefin resin solution of step ③ and stir to carry out precipitation reaction, and then filter, wash and dry to obtain a highly transparent cycloolefin resin material.

[0020] In the present invention, the recycled plastic in step ① is waste plastic containing cycloolefin copolymer (COC) and / or cycloolefin polymer (COP);

[0021] Preferably, the recycled plastic further comprises linear low density polyethylene (LLDPE) and / or low density polyethylene (LDPE).

[0022] Preferably, in terms of the mass percentage of recycled plastics, the sum of the mass of the cyclic olefin copolymer (COC) and / or cyclic olefin polymer (COP) and the linear low density polyethylene and / or low density polyethylene accounts for more than 98wt%, for example, 98.1, 98.3, 98.5, 98.7, 99, 99.2, 99.5, 99.7, 99.9wt%; wherein the mass percentage of the cyclic olefin copolymer (COC) and / or cyclic olefin polymer (COP) is 70-85wt% of the total mass of the recycled plastics, for example, 70, 75, 80, 85wt%.

[0023] The specific source of the recycled plastic is not limited, and is preferably recycled easy-tear film particles for packaging.

[0024] In the cleaning described in step ① of the present invention, the cleaning agent adopts at least one of a non-ionic surfactant cleaning agent, a zwitterionic cleaning agent, an alkaline cleaning agent, and a biological enzyme cleaning agent. It can be diluted with water during specific use, and rinsed with water after the cleaning is completed. It belongs to the conventional operation in the field, and its specific process such as temperature and time are not specifically limited, and the dirt can be cleaned.

[0025] In the present invention, the cryogenic crushing treatment in step ① has a treatment temperature of -50 to -78°C; for example, -50, -55, -60, -65, -70, -75, -78°C.

[0026] Preferably, the average particle size of the waste powder after crushing is less than 1000 μm, such as 1000, 900, 800, 700, 600, 500, 400, 300, 200, 100, 50 μm, preferably 300 to 600 μm. After the recycled waste is processed into powder of the preferred particle size, it has a higher processing efficiency in the subsequent dissolution and adsorption process, and can more effectively remove small molecular impurities and insoluble matter in the waste.

[0027] In the present invention, the mass ratio of the waste powder in step ② to the volume ratio of the solvent is 1g: (20-40) mL, for example 1g: 20 mL, 1g: 25 mL, 1g: 30 mL, 1g: 35 mL, 1g: 40 mL, preferably 1g: (20-25) mL.

[0028] The heating temperature, residence time, etc. will affect the dissolution effect of the waste material. The temperature and time satisfy the following defined relationship so that the cycloolefin resin material in the recycled plastic is fully dissolved in the solvent; When T0=60°C and t0=40min, under the conditions of the present invention, the selectivity of COC or COP in the dissolved waste powder can be improved to obtain high-purity regenerated COC or COP products.

[0029] In the present invention, the adsorbent in step ③ is at least one of activated carbon, bentonite, montmorillonite, activated white clay, and alumina.

[0030] In the present invention, the mass ratio of the adsorbent in step ③ to the waste powder in step ② is 1:(50-100), for example, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100.

[0031] Preferably, the adsorption temperature is 70-90°C, such as 70, 80, 90°C, and the adsorption time is 0.5-2h, such as 0.5, 1, 1.5, 2h. Under the above conditions, COC or COP in the waste powder can be fully dissolved in the mixed solvent, and its seeped or insoluble additive impurities such as antioxidants, colorants, etc. can be fully removed by the adsorbent, thereby improving the purity of COC or COP recycled materials.

[0032] In the present invention, the precipitant in step ④ is an acidified ethanol solution.

[0033] Preferably, the acid used for acidification in the acidified ethanol solution is one or more of hydrochloric acid, phosphoric acid, acetic acid, and formic acid. More preferably, the volume percentage content of the acid in the acidified ethanol solution is 5 to 15%, for example, 5, 7, 9, 11, 13, or 15%.

[0034] In the present invention, the volume ratio of the cycloolefin resin solution to the precipitant in step ④ is 1:(0.5-1.5), for example, 1:0.5, 1:1, 1:1.5.

[0035] In the present invention, the drying in step ④ is vacuum drying, the temperature is 80-120° C., the vacuum degree is ≤0.1 kPa, and the time is 8-12 hours.

[0036] The glass transition temperature Tg of the highly transparent cycloolefin copolymer (COC) of the present invention is 60 to 180°C;

[0037] The glass transition temperature Tg of the highly transparent cycloolefin polymer (COP) of the present invention is 100 to 160°C;

[0038] The light transmittance of the highly transparent cycloolefin resin material of the present invention is not less than 90%, for example, 90, 91, 92, 93, 94, 95, or 97%.

[0039] The purity of the highly transparent cycloolefin resin material of the present invention is ≥98.5wt%.

[0040] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0041] (1) The empirical formula proposed in the present invention achieves an effective balance between high recovery purity and high recovery efficiency of cycloolefin resin by cleverly adjusting the relationship between heating temperature and residence time, while satisfying the separation and purification of COC and COP materials, thereby improving the recycling value of cycloolefin resin materials.

[0042] (2) The method provided in the present invention has a simple process and high efficiency. Without adding additional additives, the obtained product has excellent transparency, high application value, and a wide range of applications. At the same time, the solvent can be recycled and reused, turning waste into treasure and saving costs, providing a solution for the recycling of COC or COP plastics. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] The sources of the main raw materials used in the examples and comparative examples of the present invention are as follows. Other sources are obtained from common commercial channels unless otherwise specified:

[0045] Easy-tear film granule recycled material a: COC content is 85wt% (Japan Polyplastics TOPAS8007), glass transition temperature Tg is 78℃; low-density polyethylene content is 15wt% (Maoming Petrochemical LDPE 2420H), melting point is 109℃;

[0046] Easy-tear film granule recycled material b: COC content is 80wt% (Japan Polyplastics TOPAS5013), glass transition temperature Tg is 134℃; low-density polyethylene content is 20wt% (Maoming Petrochemical LDPE 2420H), melting point is 109℃;

[0047] Easy-tear film particle recycling material c: COP content is 70wt% (Japan Zeon 1020R), glass transition temperature Tg is 102℃; low-density polyethylene content is 30wt% (Maoming Petrochemical LDPE 2420H), melting point is 109℃;

[0048] The easy-tear film granule recycled materials a, b and c are homemade, and are prepared by film blowing process according to the analysis of the components of existing easy-tear film products and conventional processing operations in the field. The specific operation is: cycloolefin resin material and low-density polyethylene are mixed in proportion, then added to the screw extruder for melt extrusion, and then directly blown into film in the film blowing machine to obtain homemade recycled materials; the temperature during the processing is controlled at 260°C, the film blowing ratio is 2, the traction speed is 30m / min, and the screw speed is 25r / min.

[0049] Adsorbent (activated carbon): Shanghai McLean Biochemical Technology Co., Ltd., 20-50 mesh;

[0050] Adsorbent (bentonite): Shanghai McLean Biochemical Technology Co., Ltd., density 2-3 g / cm 3 ;

[0051] Cleaning agent: Guangdong Sanpin Technology Co., Ltd., SP-288, non-ionic surfactant;

[0052] Decalin: Beijing Inokai Technology Co., Ltd., analytical grade;

[0053] Tetralin: Beijing Inokai Technology Co., Ltd., analytical grade;

[0054] Dimethyl sulfoxide: Beijing Inokai Technology Co., Ltd., analytical grade.

[0055] The performance test parameters and corresponding test methods used in various embodiments of the present invention are as follows:

[0056] (1) The purity (wt%) of COC or COP in recycled plastics is calculated as follows: The purity of recycled plastics was determined using a Bruker Avance III 600 MHz nuclear magnetic resonance spectrometer. 13 C NMR spectrum, and thus calculate the purity of COC or COP in the recycled plastic, using deuterated tetrachloroethane as solvent and the measurement temperature at 120 °C.

[0057] (2) The calculation formula for the recovery rate (wt%) is: 100×(mass of COC or COP in recycled plastic ÷ mass of COC or COP in waste plastic).

[0058] (3) Light transmittance: refer to GB 2410-2008 and test on a light transmittance tester.

[0059] (4) The glass transition temperature Tg of the recycled COC or COP plastic was determined by differential scanning calorimetry (DSC) with a heating rate of 10°C / min, a cooling rate of 10°C / min, a scanning range of 30 to 280°C, and a quadratic heating curve.

[0060] Example 1

[0061] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0062] ① 10g of the easy-tear film particle recycling material a was washed with cleaning agent SP-288 and water, and then rinsed with clean water. The recycled plastic was dried in an oven at 80°C (vacuum degree ≤ 0.1kPa) for 12 hours, and then crushed using a cryogenic crusher at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 300μm;

[0063] ② Add the waste powder into 106 mL of tetralin and 94 mL of dimethyl sulfoxide mixed solvent, heat to 60 ° C under stirring conditions and leave for 40 minutes to fully dissolve the COC;

[0064] ③ Then, 0.2 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 70°C for 2 h, the solid residue was removed by filtration to obtain a purified COC solution;

[0065] ④ Add 210 mL of purified COC solution to a mixture of 250 mL of ethanol and 25 mL of hydrochloric acid, stir to carry out precipitation reaction, filter and wash, and dry in an oven at 80°C (vacuum degree ≤ 0.1 kPa) for 12 hours to obtain a highly transparent COC material.

[0066] Example 2

[0067] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0068] ① Wash 20g of the easy-tear film particle recycling material a with cleaning agent SP-288 and water, then rinse with clean water, dry the recycled plastic in a 90°C oven (vacuum degree ≤ 0.1kPa) for 10h, and use a deep cold crusher to crush at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 400μm;

[0069] ② Add the waste powder into 294 mL of decalin and 126 mL of dimethyl sulfoxide mixed solvent, heat to 70 ° C under stirring conditions and leave for 19 minutes to fully dissolve the COC;

[0070] ③ Then, 0.2 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 80°C for 1 h, the solid residue was removed by filtration to obtain a purified COC solution;

[0071] ④ Add 440 mL of the purified COC solution to a mixture of 500 mL of ethanol and 50 mL of hydrochloric acid, stir to carry out precipitation reaction, filter, wash, and dry in a 90°C oven (vacuum degree ≤ 0.1 kPa) for 10 h to obtain a highly transparent COC material.

[0072] Example 3

[0073] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0074] ① 15g of the easy-tear film particle recycling material b was washed with cleaning agent SP-288 and water, and then rinsed with clean water. The recycled plastic was dried in an oven at 100°C (vacuum degree ≤ 0.1kPa) for 9 hours, and then crushed using a cryogenic crusher at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 500μm;

[0075] ② Add the waste powder into 264 mL of decalin and 66 mL of dimethyl sulfoxide mixed solvent, heat to 80 ° C under stirring conditions and leave for 9 minutes to fully dissolve the COC;

[0076] ③ Then, 0.25 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 90°C for 0.5 h, the solid residue was removed by filtration to obtain a purified COC solution;

[0077] ④ Add 345 mL of the purified COC solution to a mixture of 475 mL of ethanol and 25 mL of hydrochloric acid, stir to carry out precipitation reaction, filter and wash, and dry in an oven at 100°C (vacuum degree ≤ 0.1 kPa) for 9 hours to obtain a highly transparent COC material.

[0078] Example 4

[0079] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0080] ① 12g of the easy-tear film particle recycling material b was washed with cleaning agent SP-288 and water, and then rinsed with clean water. The recycled plastic was dried in an oven at 120°C (vacuum degree ≤ 0.1kPa) for 8h, and then crushed using a cryogenic crusher at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 600μm;

[0081] ② Add the waste powder into 144 mL of decalin and 36 mL of dimethyl sulfoxide mixed solvent, heat to 90 ° C under stirring conditions and leave for 5 minutes to fully dissolve the COC;

[0082] ③ Then, 0.125 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 70° C. for 2 h, the solid residue was removed by filtration to obtain a purified COC solution;

[0083] ④ Add 312 mL of purified COC solution to a mixture of 180 mL of ethanol and 20 mL of hydrochloric acid, stir to carry out precipitation reaction, filter and wash, and dry in an oven at 120°C (vacuum degree ≤ 0.1 kPa) for 8 hours to obtain a highly transparent COC material.

[0084] Example 5

[0085] Preparation of highly transparent cycloolefin polymer (COP) from recycled plastics, the specific steps are:

[0086] ① Wash 2.5g of the easy-tear film particle recycling material c with cleaning agent SP-288 and water, then rinse with clean water, dry the recycled plastic in a 120℃ oven (vacuum degree ≤ 0.1kPa) for 8h, and use a cryogenic crusher to crush it at -50~-78℃ (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 500μm;

[0087] ② Add the waste powder into 36 mL of tetralin and 24 mL of dimethyl sulfoxide mixed solvent, heat to 100 ° C under stirring conditions and leave for 2.5 minutes to allow the COP to fully dissolve;

[0088] ③ Then, 0.04 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 70°C for 1.5 h, the solid residue was removed by filtration to obtain a purified COP solution;

[0089] ④ Add 62.5 mL of the purified COP solution to a mixture of 65 mL of ethanol and 10 mL of hydrochloric acid, stir to perform a precipitation reaction, filter, wash, and dry in an oven at 120° C. (vacuum degree ≤ 0.1 kPa) for 8 h to obtain a highly transparent COP material.

[0090] Example 6

[0091] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0092] ① 75g of the easy-tear film particle recycling material a was washed with cleaning agent SP-288 and water, and then rinsed with clean water. The recycled plastic was dried in an oven at 100°C (vacuum degree ≤ 0.1kPa) for 9 hours, and then crushed using a cryogenic crusher at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 100μm;

[0093] ② Add the waste powder into 1890 mL of tetralin and 1110 mL of dimethyl sulfoxide mixed solvent, heat to 70 ° C under stirring conditions and leave for 19 minutes to fully dissolve the COC;

[0094] ③ Then, 1 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 80°C for 1 hour, the solid residue was removed by filtration to obtain a purified COC solution;

[0095] ④ Add 3075 mL of the purified COC solution to a mixture of 2000 mL of ethanol and 200 mL of hydrochloric acid, stir to carry out precipitation reaction, filter and wash, and dry in an oven at 100°C (vacuum degree ≤ 0.1 kPa) for 9 hours to obtain a highly transparent COC material.

[0096] Example 7

[0097] Preparation of highly transparent cyclic olefin copolymer (COC) from recycled plastics, the specific steps are:

[0098] ① 75g of the easy-tear film particle recycling material b was washed with a cleaning agent SP-288 and water, and then rinsed with clean water. The recycled plastic was dried in an oven at 100°C (vacuum degree ≤ 0.1kPa) for 9 hours, and then crushed using a cryogenic crusher at -50 to -78°C (including liquid nitrogen cooling) to obtain waste powder with an average particle size of 800μm;

[0099] ② Add the waste powder into 1530mL of decalin and 720mL of dimethyl sulfoxide mixed solvent, heat to 80°C under stirring conditions and leave for 9 minutes to fully dissolve the COC;

[0100] ③ Then, 0.9 g of adsorbent bentonite was added to adsorb impurities. After adsorption at 80°C for 1 h, the solid residue was removed by filtration to obtain a purified COC solution;

[0101] ④ Add 2325 mL of purified COC solution to a mixture of 1500 mL of ethanol and 150 mL of hydrochloric acid, stir to carry out precipitation reaction, filter and wash, and dry in an oven at 100°C (vacuum degree ≤ 0.1 kPa) for 9 hours to obtain a highly transparent COC material.

[0102] Comparative Example 1

[0103] Refer to the method of Example 2, the only difference is that the residence time of step ② is 23 min, and other conditions remain unchanged.

[0104] Comparative Example 2

[0105] The method of Example 2 was followed, except that the residence time of step ② was 15 min, and other conditions remained unchanged.

[0106] Comparative Example 3

[0107] The method of Example 3 was followed, except that the residence time of step ② was 13 min, and other conditions remained unchanged.

[0108] Comparative Example 4

[0109] The method of Example 4 was followed, except that the residence time of step ② was 11 min, and other conditions remained unchanged.

[0110] Comparative Example 5

[0111] The method is similar to that in Example 1, the only difference is that the solvent in step ② is dimethyl sulfoxide, and the other conditions remain unchanged.

[0112] Comparative Example 6

[0113] Refer to the method of Example 5, the only difference is that the solvent in step ② is tetralin, and the other conditions remain unchanged.

[0114] Comparative Example 7

[0115] Refer to the method of Example 2, the only difference is that the solvent in step ② is decalin, and the other conditions remain unchanged.

[0116] Comparative Example 8

[0117] The easy-tear film particle recycled material a is used, which is not processed by the method of the present invention, but is only processed by a simple extrusion processing method to recycle the plastic.

[0118] The cycloolefin resin materials prepared in the above examples and comparative examples were subjected to performance tests, and the test data are shown in Table 1:

[0119] Table 1 Performance test results of cycloolefin copolymers of Examples 1 to 7 and Comparative Examples 1 to 8

[0120]

[0121] It can be seen from Comparative Examples 1, 3 and 4 that if the residence time is too long, a portion of the LDPE will be accelerated to swell and then dissolve, resulting in too low purity of the recycled COP plastic.

[0122] It can be seen from Comparative Example 2 that if the residence time is too short, the solvent will not be able to fully dissolve COC, and the purity of the recycled COC plastic will be too low.

[0123] It can be seen from Comparative Examples 5-7 that replacing the mixed solvent with a single solvent will result in the solvent being unable to fully dissolve COC, resulting in the recycled COC plastic having too low purity.

[0124] It can be seen from Comparative Example 8 that when other methods are used to recycle plastics, low-density polyethylene and COC cannot be completely separated, resulting in the recycled COC plastic having too low purity.

Claims

1. A method for separating and purifying cycloolefin resin materials from recycled plastics, the method comprising maintaining the recycled plastics in a solvent at a certain temperature and time, wherein the temperature and time satisfy the following defined relationship, so that the cycloolefin resin materials in the recycled plastics are fully dissolved in the solvent; n≥0; where T0 and T n are a certain temperature and the next elevated temperature; t0 and t n They correspond to specific temperatures T0 and T n The residence time under T0 is 40min when T0 is 60℃.

2. The method according to claim 1, characterized in that The cycloolefin resin material is a cycloolefin copolymer (COC) or a cycloolefin polymer (COP).

3. The method according to claim 1 or 2, characterized in that The solvent is a mixed solvent selected from decalin and dimethyl sulfoxide or tetralin and dimethyl sulfoxide. Preferably, the volume fraction of decalin in the mixed solvent of decalin and dimethyl sulfoxide is 68-80% of the total volume of the mixed solvent, and the volume fraction of tetralin in the mixed solvent of tetralin and dimethyl sulfoxide is 53-63% of the total volume of the mixed solvent.

4. The method according to any one of claims 1 to 3, characterized in that: The method comprises the following specific steps: ① Wash, dry and deep-cryogenically crush the recycled plastics to obtain waste powder; ② Mix the waste powder with the solvent, heat it to a certain temperature under stirring conditions and keep it for a specific time; ③ adding an adsorbent to the mixed material of step ② for adsorption, and then collecting to obtain a purified cycloolefin resin solution; ④ Add a precipitant to the purified cycloolefin resin solution of step ③ and stir to carry out precipitation reaction, and then filter, wash and dry to obtain a highly transparent cycloolefin resin material.

5. The method according to claim 4, characterized in that Step ① The recycled plastic is waste plastic containing cyclic olefin copolymer (COC) and / or cyclic olefin polymer (COP); the recycled plastic also contains linear low-density polyethylene (LLDPE) and / or low-density polyethylene (LDPE); Preferably, in terms of the mass percentage of recycled plastics, the sum of the mass of the cyclic olefin copolymer (COC) and / or cyclic olefin polymer (COP) and the linear low-density polyethylene and / or low-density polyethylene accounts for more than 98wt%; and / or the mass percentage of the cyclic olefin copolymer (COC) and / or cyclic olefin polymer (COP) is 70-85wt% of the total mass of the recycled plastics.

6. The method according to claim 4 or 5, characterized in that The deep cold crushing treatment in step ①, The processing temperature is -50 to -78°C; the average particle size of the waste powder after the crushing process is less than 1000 μm.

7. The method according to any one of claims 4 to 6, characterized in that: In step ②, the mass ratio of the waste powder to the volume ratio of the solvent is 1 g: (20-40) mL, preferably 1 g: (20-25) mL.

8. The method according to any one of claims 4 to 7, characterized in that: The adsorbent in step ③ is at least one of activated carbon, bentonite, montmorillonite, activated white clay, and alumina; and / or, the mass ratio of the adsorbent in step ③ to the waste powder in step ② is 1:(50-100), for example, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100; and / or, the adsorption temperature is 70-90°C, and the adsorption time is 0.5-2h.

9. The method according to any one of claims 4 to 8, characterized in that: In step ④, the precipitant is an acidified ethanol solution; preferably, the acid used for acidification in the acidified ethanol solution is one or more of hydrochloric acid, phosphoric acid, acetic acid, and formic acid. More preferably, the volume percentage of the acid in the acidified ethanol solution is 5 to 15%.

10. The method according to any one of claims 4 to 9, characterized in that: The volume ratio of the cycloolefin resin solution to the precipitant in step ④ is 1:(0.5-1.5); and / or, the drying in step ④ is vacuum drying at a temperature of 80-120° C., a vacuum degree of ≤0.1 kPa, and a time of 8-12 h.

Citation Information

Patent Citations

  • Methods for purifying contaminated polymers

    CN107810226B

  • Method for purifying cycloolefin copolymer from plastic reclaimed material

    CN114133618A

  • Solvent-based process for post-consumer recycling of polyethylene terephthalate

    CN117279986A

  • Method for preparing high-transparency cycloolefin copolymer from recycled plastic, high-transparency cycloolefin copolymer prepared by method and application of high-transparency cycloolefin copolymer

    CN117801360A

  • Method of separating solvent from thermoplastic resin

    JP2002264129A